STRATEGI KOMUNIKASI PIMPINAN MENGENAI PROGRAM E- ABSENSI DALAM MENINGKATKAN KEDISIPLINAN PEGAWAI KANTOR DISKOMINFO KOTA DUMAI - Syahrul Irvandi; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Diskominfo is one of the Dumai city government agencies that is committed to realizing electronic government within the scope of the Dumai City Government. The application of E-Absence is also in line with Mayor Regulation Number 8 of 2021 regarding the provision of additional income for employees within the Dumai City Government. The purpose of this study was to find out how the communicator strategy, message strategy, media strategy, audience strategy, the response/effect of the leader's communicant regarding the E-Absence program in increasing the discipline of the Dumai City Diskominfo office employees. This study uses a qualitative descriptive method using a strategic communication model. The research subject is the Head of the Communication and Information Technology office, as well as office employees. The object in this study is the leadership communication strategy regarding Website-based E-Attendance in increasing employee discipline by using interview, observation, and research documentation data collection techniques. triangulation. Data analysis techniques are: data presentation, comparison, and drawing conclusions. The strategy for selecting communicators is based on warrants and based on the factors that communicators must have, message strategies are grouped into two, namely informative messages in the form of appeals about switching attendance systems from manual to digital, and persuasive messages in the form of invitations from the head of department to be adaptive in implementing the new system In this case, there are two media strategies, the first is using online media in the form of websites and social media, namely Instagram and Facebook, the audience selection strategy is employees of the Dumai City Diskominfo office and other regional apparatus organizations as well as responses. The response given by the audience is a positive response, namely appreciation by leadership employees who are considered very appropriate in conveying messages so that employees are able to accept and adapt. Keywords: Communication strategy, Leaders, E-Absensi, Dumai City Discominfo